The 4‐Hour Rule: An ENT Perspective. (23rd August 2013) - Ha, Jennifer; Lu, Png H.; Chapman, Kate; Friedland, Peter
Abstract : Objectives: The pervasive theme in Western Australian medicine in 2011/2012 was the newly introduced 4‐hour rule in emergency departments. This article approaches the various issues and problems from an ear, nose, and throat (ENT) perspective, with subsequent recommendations. Methods: We performed a retrospective audit looking at the most commonn ENT diagnoses according to the ICD‐10‐AM classification: acute pharyngitis, streptococcal tonsillitis, acute tonsillitis, and peritonsillar abscess. Patients looked at included those who presented 6 months before and after the 4‐hour rule implementation. Results: We found a decreased diagnostic accuracy (41.2% vs 28.6%), reduced intravenous hydration commencement (94.1% vs 64.3%), and reduced intravenous antibiotics commencement (70.6% vs 50.0%). Conclusions: Although positivity has been seen within certain aspects of patient outcomes since the introduction of the 4‐hour rule, certain inherent issues must be acknowledged. Recommendations and modifications have been suggested as possible alternatives.